Case Report: Prolapsed Ureterocele—A Differential Diagnosis of Urethral Cists - Francisco Renan Doth Sales; Georgia Alexsandra Colantonio Dourado; Ana Carolina Montes Ribeiro; Humberto de Holanda Madeira Barros; David Sucupira Cristino; Antonio Augusto Guterres Castro; Francisco José Cabral Mesquita (Case Reports in Urology)
Ureterocele is a cystic dilatation of submucosal distal ureter. It presents a higher incidence in infants and young children but is rare in adults. The urethral prolapse of ureterocele is extremely rare, and its clinical presentation includes vulvar mass, hematuria, and urinary tract dysfunction. We present a case of ureterocele prolapse in a 45-year-old woman who has a 3-day-evolution vulvar mass and intense urethral bleeding. The patient underwent armed cystoscopy and ureteroscopy, ureterocele resection, and biopsy. She evolved with good postoperative condition and was then discharged.